The effectiveness of advertising in digital marketing towards customer satisfaction - Bakri, Mohammed Hariri; Zamli, Nurul Syazwanie; Azman, Hartini (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
The advertising in digital marketing nowadays more closer to the consumer so it highlight the relationship of the effectiveness advertising in digital marketing with customer satisfaction. This research aim to investigate the effectiveness of advertising in digital marketing towards customer satisfaction in Melaka, Malaysia. This study had been mainly adopted from SERVQUAL model. Thus, Tangibility features, Reliability, Responsiveness, Assurance and Empathy were the focused factor in this research. Quantitative data had been collected through the questionnaire. A total of 384 respondents who live in Melaka City area were participated in this research by using simple random sampling techniques. Software Package for Social Science (SPSS) was used to analyse the collected data. The data analysis techniques that conducted in study were descriptive analysis, Pearson correlation and multiple regression analysis to describe the variables numerically and found out the relationship between independent variables and dependent variable. The results showed that all the factors had significantly influenced customer satisfaction toward advertising in digital marketing. Assurance was the most influencing factor and all the research objectives had been achieved in this study. The findings would contribute for practitioners to have a clear understanding and become more consumer-sensitive to create positive attitude from consumers. Implications and recommendations for further research were also mentioned in this study.